KONSEP-KONSEP DASAR SISTEM INFORMASI - Jabbar, Muhammad Iqbal Abdul (PMPP Lembaga Penelitian dan Studi Kebijakan, 2025)
The Higher Education Management Information System (SIMPT) is a strategic instrument in supporting decision-making, operational efficiency, and improving the quality of governance of higher education institutions. This study aims to identify and analyse the main components of SIMPT and their relationship in supporting managerial and academic performance of higher education institutions. The method used was literature study and descriptive analysis of various models of higher education information systems. The study results show that SIMPT consists of four main components, namely hardware, software, operational procedures, and brainware (system users). The four components must be integrated in order to create a reliable and adaptive information system. In addition, institutional policies, data security, and HR training also play an important role in supporting system effectiveness. A well-managed SIMPT can improve transparency, accountability, and competitiveness of higher education institutions